Inexplicable Sex Differences in Homonegativity: A Proposed New Paradigm of Implicit Cognitive Systems - Stanfield, Candice T.; J, Harvey (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Sex differences in self-reported homonegativity is prevalent in past research, yet unexplained. We examined possible factors associated with sex differences in overall homonegativity. Heterosexuals self-reported on scales including variables of differential exposure to homosexuals, disgust sensitivity, and reporting biases. Males consistently expressed more negative attitudes toward homosexuals, especially gay men. Many variables were significantly correlated with overall homonegativity and revealed significant sex differences, however, unconvincingly. Self-report measures may lack validity, not always capturing peoples true attitudes. Utilizing a new paradigm of implicit cognitive systems may be more worthwhile in explaining social psychological representations of the abstract cognitive construct of prejudice/stereotyping.